Dose escalation study of proton beam therapy with concurrent chemotherapy for stage III non‐small cell lung cancer. Issue 7 (20th June 2016) - Harada, Hideyuki; Fuji, Hiroshi; Ono, Akira; Kenmotsu, Hirotsugu; Naito, Tateaki; Yamashita, Haruo; Asakura, Hirofumi; Nishimura, Tetsuo; Takahashi, Toshiaki; Murayama, Shigeyuki
Abstract : The purpose of this study is to determine the recommended dose (RD) of proton beam therapy (PBT) for inoperable stage III non‐small cell lung cancer (NSCLC). We tested two prescribed doses of PBT: 66 Gy (relative biological effectiveness [RBE]) in 33 fractions and 74 Gy (RBE) in 37 fractions in arms 1 and 2, respectively. The planning target volume (PTV) included the primary tumor and metastatic lymph nodes with adequate margins. Concurrent chemotherapy included intravenous cisplatin (60 mg/m 2, day 1) and oral S‐1 (80, 100 or 120 mg based on body surface area, days 1–14), repeated as four cycles every 4 weeks. Dose‐limiting toxicity (DLT) was defined as grade 3 or severe toxicities related to PBT during days 1–90. Each dose level was performed in three patients, and then escalated to the next level if no DLT occurred. When one patient developed a DLT, three additional patients were enrolled. Overall, nine patients (five men, four women; median age, 72 years) were enrolled, including six in arm 1 and three in arm 2. The median follow‐up time was 43 months, and the median progression‐free survival was 15 months. In arm 1, grade 3 infection occurred in one of six patients, but no other DLT was reported. Similarly, no DLT occurred in arm 2. However, one patient in arm 2 developed grade 3 esophageal fistula at 9 months after the initiation of PBT. Therefore, we determined that 66 Gy (RBE) is the RD from a clinical viewpoints. (Clinical trial registration no. UMIN000005585) Abstract : This is a dose‐finding study for locally advanced non‐small cell lung cancer using proton beam therapy and concurrent chemotherapy. We tested two doses of proton beam therapy, namely 66 Gy(RBE) and 74 Gy (RBE). From overall clinical viewpoints, 66 Gy (RBE) was determined as the recommended dose for future clinical trials.